Vectorcardiography: A Tool for Non-invasive Detection of Reperfusion and Reocclusion? - Eriksson, Sven V. (Thrombosis and Haemostasis, 1999)
In acute myocardial infarction, the perfusion status frequently fluctuates with rapid occurrences of coronary occlusion followed by myocardial ischemia. In patients with unstable angina, most episodes of ischemia are not accompanied by chest pain. In these patients it is important to be able to monitor the results of medical treatment non-invasively to establish the need for further intervention. It is not feasible to perform coronary angiography in all patients with acute myocardial infarction to evaluate patency of the infarct-related artery. Furthermore, even in a patent artery, no reflow may be present in the myocardial tissue. Angiography is therefore not the perfect golden standard to compare noninvasive ischemia monitoring with. Prognosis seems to be a better standard for comparison. This review indicates that vectorcardiography monitoring may identify myocardial reperfusion at an early stage and gives valuable prognostic information both in patients with unstable angina and acute myocardial infarction with low interobserver variability.
Keywords: Vectorcardiography; electrocardiography; reperfusion; ischemiamonitoring; myocardial infarction; coronary artery disease